ECORESISTANCE TO COLONIALISM IN THE POEM "FAKKIR BIGHAYRIKA" BY MAHMOED DARWISH (POSTCOLONIAL STUDIES) - Ikhwanul Habib; Sintya Rahmadewi; Taqiyuddin Kabalmay; Muhibbuddin S (Journal of Arabic Literature (JaLi), 2025)
This problem addresses how Mahmoud Darwish's poetry expresses symbolic resistance through ecological, empathic, and spiritual narratives that are grounded in the collective suffering of the Palestinian people. The purpose of this research is to reveal the meaning of colonialism and ecoresistance ideologically and rhetorically as a form of resistance to colonial hegemonic narratives. This research uses contextual qualitative analysis method with triangulation of sources and theories, through documentation and literature study. The results show that natural symbols such as water, trees, and light become markers of spiritual and ecological attachment to the homeland as well as a form of resistance to colonialism. Religious elements strengthen the legitimacy of transcendent and collective resistance. This poem conveys that resistance can take the form of empathy, solidarity, and existential awareness. This article contributes to a new reading of Darwish's poetry by combining ecological, spiritual and postcolonial dimensions. The findings are relevant for Middle Eastern literary studies and cultural conflict studies.